Diversidade genética de isolados ambientais de Vibrio cholerae da Amazônia brasileira - SÁ, Lena Líllian Canto de (Universidade Federal do Pará, 2014)
Vibrio cholerae, the etiologic agent of cholera, is an autochtonus bacterium of aquatic environment in temperate and tropical regions of the world. Cholera is endemic and epidemic in many countries in Africa, Asia and Central and South America. In this study our goal was to detemine the genetic diversity of V.cholerae environmental isolates from aquatic ecosystems in the Amazon region of Brazil. A total of 148 environmental strains of V.cholerae non-O1 and non-O139 (NAG) and O1 serogroups, isolated from the Amazon region since 1977 to 2007, were characterized and compared with clinical strains of V.cholerae O1 from sixty and seventh cholera pandemic. PFGE (pulsed-field gel electrophoresis) was performed to determine the clonal relationships between V.cholerae non-O1, O1 environmental and clinical strains. The presence of virulence genes (hlyA/hem, hlyB, hlyC, rtxA, rtxC, tcp, ctx, zot, ace, stn/sto) and class 1, 2 and 3 integrons (intI 1, 2 e 3) was analyzed by polymerase chain reaction. Whole genome macrorestriction analysis revealed that the environmental V.cholerae NAGs were more diverse than the environmental O1 strains, both groups segregate in distinct clusters and most of environmental O1 strains show a clonal relationship with seventh cholera pandemic strains. The distribution of virulence genes in NAGs strains is largely different from that of O1 strains which, in general, were positive for all virulence genes analyzed excepting for stn/sto and class 1, 2 and 3 integrons. Some O1 environmental strains, belonging to the seventh pandemic lineage, went through an extensive gene loss. Distinct NAGs strains were stn/sto+ and intI 1+. Two alleles of aadA were found: aadA2 and aadA7. Interestingly, V.cholerae O1 environmental strains belonging to the pandemic lineage were only isolated during the period of cholera epidemic in the Amazon region of Brazil (1991-1996).